2011
DOI: 10.1016/j.seizure.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Elderly patients with epileptic seizures: In-patient observational study of two French community hospitals

Abstract: Epileptic seizures (ESs) in the elderly are recognized as frequent, and potentially difficult to diagnose. Their clinical features and relevant diagnostic problems still remain poorly investigated in hospital populations outside the setting of tertiary referral centres. In this study we attempted to improve the understanding of these aspects in community institutions. We conducted a four-year retrospective observational study of 104 consecutive elderly patients with the diagnosis of ES, in 2 French community h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…Epileptic seizures in patients above 60 years of age had a positive response to the monotherapy 13 . The infrequent use of lamotrigine is related to the fact that the sample of the study was taken from a public health service with limited financial resources.…”
Section: Discussionmentioning
confidence: 98%
“…Epileptic seizures in patients above 60 years of age had a positive response to the monotherapy 13 . The infrequent use of lamotrigine is related to the fact that the sample of the study was taken from a public health service with limited financial resources.…”
Section: Discussionmentioning
confidence: 98%
“…To characterize the presentation of the ES, the following definitions proposed by Massengo et al 6 were used in this study: status epilepticus (SE) -a more prolonged ES or a sequence of ES without complete recovery of consciousness between them -and ES in series -various ES in one day.…”
Section: Discussionmentioning
confidence: 99%
“…Such episodes can be difficult to characterize, leading to confusion with dementias, memory lapses and even with episodes of mental confusion 9 . Thus, the diagnosis of ES may be retarded or may even not be made, as occurs in about 30% of the cases 3,6,[9][10][11] . Some authors have suggested that complex ES in the elderly present a ictalsemiology distinct from that found in the young adult, since in the elderly the localization most frequently found involves the frontal and parietal lobes and not the temporal lobe 4,12 .…”
Section: Epileptic Seizuresmentioning
confidence: 99%
See 2 more Smart Citations